KEDUDUKAN HUKUM KEWENANGAN PENGABSAHAN PROSES MANAJEMEN PEGAWAI NEGERI SIPIL BAGI PEJABAT FUNGSIONAL ANALIS KEPEGAWAIAN - Jauhir Jauhir (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2018)
The Civil Servant Management aims to produce professional civil servants who have a basic value, professional ethics, politic intervention free, corruption, collusion, and nepotism free. It covers preparation and determination of needs, procurement, rank and position, career development and pattern, promotion, mutation, performance assessment, payroll and benefits, appreciation, discipline, dismissal, pension guarantee and plan, and protection process. All of the above processes become the main task of employment analyst functional officer (Analis Kepegawaian) based on applicable laws and regulations. But in feet those processes have been done also by administration officer and high-rank officer, so it makes an authority duplication. As the result, there was validation authority duplication between employee analyst with administration officer and high-rank officer the civil servant management process, so this result makes a conclusion that validation authority of civil servant management processbecome an authority for employee analyst because it has a strong legal basis based on applicable laws and regulations. While the regulation authority between employee analyst with administration officer and high-rank officer should be restored and regulated by ethic code and professional ethic of each position.